The economics of sports - Kahane, Leo H.; Shmanske, Stephen, 1954- (New York ; Oxford : Oxford University Press, 2012)
Shmanske and Kahane have organized over 50 essays from prominent sports economists into two volumes around two related themes. This first volume explains how economics aids sports through the systematic application of economic theory and logic to the institutions in sports.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Sports -- Economic aspects